Concurrent and Longitudinal Correlation Between Children’s Emotional Reactivity, Regulation and Adjustment - Trần, Thành Nam (H. : ĐHQGHN, 2017)
This paper describes a study using two different samples to examine concurrent and longitudinal relations between children’s emotional reactivity, regulation and adjustment. Forty-eight children from preschool through second grade were recruited to provide data on concurrent relations between regulation, reactivity and adjustment (sample 1). And forty kindergarten children were recruited and assessed at 2 time points to provides longitudinal relations (sample 2). Emotional reactivity and regulation were assessed during home visits using the same series of disappointment tasks, questionnaires and coding system. In sample 1, teachers completed a problem behavior checklist at the same time with the home visit. In sample 2, teachers completed the checklist two years after home observation. Results indicate that the dysregulation of sadness is associated with internalizing behavior concurrently, and that the dysregulation of anger is associated with externalizing problems two years later. Children’s anger reactivity is associated with both concurrent and later externalizing problems.